2013
DOI: 10.1158/1940-6207.capr-12-0278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise on Markers of Inflammation in Breast Cancer Survivors: The Yale Exercise and Survivorship Study

Abstract: Physical activity is associated with improved breast cancer survival, but the underlying mechanisms, possibly including modification of the inflammatory state, are not well understood. We analyzed changes in interleukin (IL)-6, C-reactive protein (CRP), and TNF-α in a randomized controlled trial of exercise in postmenopausal breast cancer survivors. Seventy-five women, recruited through the Yale-New Haven Hospital Tumor Registry, were randomized to either a six-month aerobic exercise intervention or usual care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 63 publications
2
80
0
5
Order By: Relevance
“…For example, simple citation tracking from the systematic review by L€ of and colleagues via Google Scholar identifies two additional trials with further data about the effect of exercise on numerous inflammatory mediators (15,16). Further trials may be identified by rigorous searching.…”
Section: Introductionmentioning
confidence: 99%
“…For example, simple citation tracking from the systematic review by L€ of and colleagues via Google Scholar identifies two additional trials with further data about the effect of exercise on numerous inflammatory mediators (15,16). Further trials may be identified by rigorous searching.…”
Section: Introductionmentioning
confidence: 99%
“…The IL-6 expression in breast tissue is associated with the grade of the tumor (10,11). Previous studies have shown that, compared to healthy women, breast cancer survivors have higher amounts of circulating cytokines, a disorder that may persist for up to five years after the diagnosis of cancer (12). Obesity, being overweight and inactivity are among factors that cause mild chronic inflammation and can increase the risk of cardiovascular diseases, breast cancer recurrence and death in breast cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…This risk factor is further highlighted by the fact that the majority of breast cancer survivors are overweight or obese. The combination of being overweight and inactive has been attributed to a quarter of all the cases of cancer (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…As in our study, low-risk patients in the Ezaz study still experienced cardiotoxicity, which suggests that even patients at low clinical risk would require monitoring to detect tic. Other tools currently used to evaluate the risk of cardiotoxicity include biomarkers such as cardiac troponin and brain natriuretic peptide 19 , global longitudinal strain imaging using echocardiography 20 , and lifestyle factors 21 . A potential avenue for future research is to determine whether clinical risk scores can be used to modulate the intensity of cardiac imaging and biomarker testing, with monitoring being less frequent in low-risk patients compared with high-risk patients.…”
Section: Discussionmentioning
confidence: 99%